Group rationality in scientific research - Sarkar, Husain (Cambridge University Press, 2007)
Under what conditions is a group of scientists rational? How would rational scientists collectively agree to make their group more effective? What sorts of negotiations would occur among them and under what conditions? What effect would their final agreement have on science and society? These questions have been central to the philosophy of science for the last two decades. In this 2007 book, Husain Sarkar proposes answers to them by building on classical solutions - the skeptical view, two versions of the subjectivist view, the objectivist view, and the view of Hilary Putnam. Although he finds these solutions not completely adequate, Sarkar retrieves what is of value from them and also expropriates the arguments of John Rawls and Amartya Sen, in order to weave a richer, deeper, and more developed theory of group rationality.